My grandfather's blessings : stories of strength, refuge, and belonging - Remen, Rachel Naomi (New York : Riverhead Books, 2000)
The author shares her insights into the kabbalistic Judaism of her grandfather, serving up a series of inspiring stories about the spiritual life.
Keywords: Jewish ethics